The Role of the Discovering Democracy Program in Addressing Citizenship and Civic Education Issues in Australia - Liana Anisa Putri; Muhammad Muslim Hidayatulloh (International Journal of Technology and Education Research, 2025)
In the 1960s Australia experienced a decline in the teaching of Civics Education. Some problems in civic education in Australia such as national identity, too much weight on Civics learning and the most serious is the lack of youth participation in citizenship. In the 1990s civic education experienced a revival, this was marked by the emergence of the Discovering Democracy program which was created to overcome existing problems. Using the literature study method, researchers examined the role of the Discovering Democracy program in Australia. Deficiencies in the understanding and skills of some teachers in the field of civic education are the focus of revamping this program. The aim is to equip young people with the necessary skills to better participate through education in schools. One way to achieve this goal is to involve students in their everyday environment. This program has a large contribution in citizenship education in Australia. Many schools report that, after this program teachers feel much more confident to teach citizenship and citizenship than before.